Pendidikan Anak Usia Dini: Integrasi Nilai-Nilai Islam dalam Perspektif Ibnu Sina : indonesia - Fadlan, Achmad; Sapriya Utami,; Nurlinda, Nurlinda; Atika Wirdasari, (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Early childhood education plays a vital role in character and moral development. This study aims to analyze Ibn Sina's ideas on integrating Islamic values in early childhood education using a holistic approach that includes spiritual, intellectual, and emotional aspects. The method employed is literature review through a descriptive qualitative approach to evaluate the relationship between Ibn Sina's educational concepts and the current early childhood education curriculum. The findings indicate that the development of morals, the enforcement of monotheism, and the practice of worship from an early age form a strong foundation for children's growth. The application of Islamic values is carried out through daily habits, Islamic thematic education, and examples set by teachers and parents. Therefore, Ibn Sina's thoughts are highly relevant as a reference for developing character education in early childhood based on Islamic values to produce intelligent, well-rounded, and faithful generations.